Human meibum and tear film derived (O-acyl)-omega-hydroxy fatty acids in meibomian gland dysfunction - Khanal, Safal; Ngo, William; Nichols, Kelly K.; Wilson, Landon; Barnes, Stephen; Nichols, Jason J. (The ocular surface, 2021)
The molecular basis of the tear film and lipid layer alterations in meibomian gland dysfunction (MGD) is unknown. This study aimed to identify and compare (O-acyl)-omega-hydroxy fatty acids (OAHFAs) derived from human meibum and tears in MGD. Of 195 eligible subjects (18–84 years, 62.6% female), 183 and 174 provided samples for tears and meibum, respectively. Subjects were classified into four groups: Normal, Asymptomatic MGD, MGD, and Mixed. Samples from the right eye of each subject were infused into the SCIEX 5600 TripleTOF mass spectrometer in negative ion mode. Lipid intensities identified with Analyst1.7 TF and SCIEX LipidView1.3 were normalized by an internal standard and total ion current, then statistically compared in MetaboAnalyst 4.0. In meibum and tears, 76 and 78 unique OAHFAs were identified, respectively. The five most frequent and abundant OAHFAs were 18:2/16:2, 18:1/32:1, 18:1/30:1, 18:2/32:1, and 18:1/34:1. Two OAHFAs, 18:2/20:2 and 18:2/20:1, were identified only in tears. Initial univariate analysis revealed three differently regulated OAHFAs in meibum and eight in tears. Partial Least Square Discriminant Analysis showed 18:1/32:1, 18:2/16:2, 18:1/34:1 and 18:0/32:1 in tears, and 18:2/16:2, 18:1/32:1 and 18:2/32:2 in meibum, had variable importance in projection scores >1.5 and contributed the most to the separation of groups. In both meibum and tears, all OAHFAS except 18:2/16:2 were reduced in MGD compared to the normal group. MGD is accompanied by differential expression of specific OAHFAs in meibum and tears. These results suggest OAHFAs play a role in the altered biochemical profile of the tear film lipid layer in humans with MGD.